Reexamining Alexander Mclearn’s Role In Adventist Education: Implications For Adventist Education Today - Sinaga, Yoanes (Fakultas Filsafat Universitas Advent Indonesia, 2025)
This article examines the controversial leadership of Alexander McLearn as President of Battle Creek College (1881–1882) and its relevance for renewing Adventist education in Indonesia’s Merdeka Belajar era. McLearn, a former Baptist minister turned Seventh-day Adventist, clashed with Goodloe Harper Bell over student discipline and gender relations, reflecting tensions between tradition and educational reform in early Adventist schooling. Using a biographical narrative method and archival sources, this study analyzes McLearn’s student-centered disciplinary approach, which anticipated Ellen G. White’s holistic educational philosophy but conflicted with institutional norms. The findings emphasize the importance of flexible leadership and character-based discipline. In response to declining enrollment in Indonesian Adventist schools, this article reinterprets McLearn as a misunderstood innovator and suggests integrating digital learning with Adventist values to address contemporary educational challenges. .